THE EFFECT OF THE COLLABORATIVE TECHNOLOGY-ENHANCED ACTIVITIES ON STUDENTS’ MOTIVATION - Alioon, Yasaman (PEOPLE: International Journal of Social Sciences, 2020)
The collaborative technology-enhanced activities developed for Algorithm Calculation course in Medical engineering subject-discipline and Computer Workshop courses in two Computer and IT engineering subject-disciplines in two consecutive semesters. Mixed-method research design was used in this study .Content of each course was used in order to develop the activities. Motivational Strategies for Leaning Questionnaire (MSLQ) was utilized for collecting quantitative data while qualitative data was collected using interview protocol for further investigation. The analyses showed that the “intrinsic value” was the category with the higher mean score for all students with three different subject-disciplines which is followed by cognitive strategy use. Moreover, the results showed that the students’ level of anxiety decreased after using the activities. Analysis of interview data showed that the students emphasized on the role of activities in terms of increasing their “collaboration” with their peers and instructor. Moreover, they perceived that the activities make the course more interesting for them. They also explained that using computerized devices especially mobile ones facilitated their communication and material-sharing.